KARAKTERISTIK BIODIESEL DARI MINYAK BIJI RANDU (CEIBA PENTANDRA) PADA REAKTOR BATCH BERPENGADUK BERTEKANAN MENGGUNAKAN KATALIS KOH - Erliyanti, Nove Kartika (Universitas Nahdlatul Ulama Sidoarjo, 2016)
Biodiesel is fuel from plant oils that has been converted into methyil ester with transesterification process. The research was aimed at investigating the influence of KOH concentration and reaction time on the characteristics (density and viscosity) biodiesel at a pressure of 4 bar. The process of making biodiesel in a stirred batch reactor is pressurized, purged nitrogen, and the temperature operation of 60°C. The kapok seed oil used as raw material was 1000, methanol, and KOH (concentration of 0.5; 1.0; 1.5; and 2% oil by weight) were mixed and put into a reactor with a reaction time of 0.25; 0.50; 1.00; and 1.50 hours. Products were analyzed according to ASTM standard. KOH concentration and reaction time has a significantly affected with respect to the density and viscosity of biodiesel. Biodiesel produced in compliance with the ASTM standard. The highest density and viscosity resulting in 0.5% KOH concentration and reaction time of 0.25 hours is equal to 0.8918 g / cm3 and 4.989 cSt.